2020
DOI: 10.31539/jks.v4i1.1604
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Berat Badan pada Remaja Obesitas Menggunakan Hipnoterapi

Abstract: This study aims to determine the effect of hypnotherapy on weight loss in obese adolescents. The research design used is a quasi-experiment. The results showed that 15 respondents (68.2%) experienced weight loss, and seven respondents (31.8%) did not experience weight loss from the statistical test results obtained p-value 0.001 with a correlation coefficient value of 0.682. Also, the p-value of the chi-square test results is 0.004. In conclusion, there is a significant relationship between hypnotherapy and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…The results of this study are also in accordance with research conducted by (Rodiani, 2019) entitled "Policystic Ovary Syndrome: Risk of Infertility that can be Prevented through Weight Loss in Obese Women" reported that lifestyle modifications, one of which is reducing weight and belly fat by reducing calorie intake. This is proven to reduce androgen levels, reduce insulin resistance so that it is expected to restore the frequency and amplitude of LH in normal amounts so that the menstrual cycle can run normally so that it is expected to reduce the risk of infertility in polycystic ovarian syndrome (PCOS).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are also in accordance with research conducted by (Rodiani, 2019) entitled "Policystic Ovary Syndrome: Risk of Infertility that can be Prevented through Weight Loss in Obese Women" reported that lifestyle modifications, one of which is reducing weight and belly fat by reducing calorie intake. This is proven to reduce androgen levels, reduce insulin resistance so that it is expected to restore the frequency and amplitude of LH in normal amounts so that the menstrual cycle can run normally so that it is expected to reduce the risk of infertility in polycystic ovarian syndrome (PCOS).…”
Section: Discussionsupporting
confidence: 89%
“…Latin America and the Caribbean have about a 1.5% primary infertility rate. Infertility in Asia is highest in Turkmenistan at 43.7% and 21.3% in Indonesia (Puspitasari, 2018 ;Rodiani, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Children who are overweight have adverse physical and psychological effects [24]. Weight loss can also be accomplished with the hypnotherapy method [25]. Science about healthy living, especially food consumption, is an essential factor in controlling children's weight [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is described as a state where clients in an unconscious state can receive suggestions from other sources. This can increase memory and reasoning power, as well as function as a tool to heal and improve other aspects of the quality of daily life and a good self-image (Rini, Hardika, and Suryani 2020). In contrast, the therapy discussed here is psychotherapy, which is defined as a type of healing that uses specific techniques to treat patients.…”
Section: Literature Reviewmentioning
confidence: 99%